A study of traditional blood lime mortar for restoration of ancient buildings. (October 2015) - Fang, Shiqiang; Zhang, Kun; Zhang, Hui; Zhang, Bingjian
Abstract: Aerial lime-based mortars are recommended by many experts to restore the ancient buildings due to their great compatibility with ancient building materials. But their shortages (like long hardening time, relatively low mechanical strength, high water absorption capacity, etc.) limited their application in many fields. In this paper, the performance and mechanism of different simulated blood mortars are presented. The results showed that the mortar prepared by blood with lime had better binding strength, waterproof property, weather resistance and curing speed than common lime mortar. Through the conductivity, FT-IR, XRD, SEM, TG and curing speed test, it was found that the excellent performance of blood lime mortar was caused by the hydrolysis of blood proteins under alkaline condition and their special multilayer structure.